Delivering a new diagnosis of Down syndrome: Parent experience. Issue 12 (1st July 2021) - Lehman, April; Leach, Mark; Santoro, Stephanie L.
ABSTRACT: Down syndrome is one of the most common chromosomal abnormalities. In 2014, in conjunction with the passing of House Bill 552, the Ohio Department of Health released a Down syndrome fact sheet to be given to parents at time of diagnosis to answer basic questions regarding the diagnosis. Our survey helps us to understand parental experience in receiving a new Down syndrome diagnosis including information provided. An electronic survey was created and distributed to members of established Down syndrome parent groups in Ohio. Questions assessed the parental experience at the time of receiving a Down syndrome. We also looked at parent perceptions after the implementation of a Down syndrome fact sheet. Responses were collected regarding experience at the time of diagnosis and broadly categorized into a trichotomy of positive experience (>5), neutral experience (=5), and negative experience (<5). Parents report an overall negative experience when receiving a new diagnosis of Down syndrome (mean of 4 on scale of 0–10), which did not increase after 2014 ( p >0.05). Eighty‐five percent of parents with children born in 2014 or after report that they did not receive the Ohio Department of Health Down syndrome fact sheet. Legislation regarding a diagnosis of Down syndrome exists in 20 states with significant variability, readability of those fact sheets. Legislation requiring accurate information be given to families was not always followed, and printed literature alone did not correlate with improved parent experience; additional efforts are necessary to ensure that the experience receiving a diagnosis of Down syndrome is not a negative one.